Air Pollution Exposure During Pregnancy and Symptoms of Attention Deficit and Hyperactivity Disorder in Children in Europe. Issue 5 (September 2018) - Forns, Joan; Sunyer, Jordi; Garcia-Esteban, Raquel; Porta, Daniela; Ghassabian, Akhgar; Giorgis-Allemand, Lise; Gong, Tong; Gehring, Ulrike; Sørensen, Mette; Standl, Marie; Sugiri, Dorothee; Almqvist, Catarina; et al.
Abstract : Background: Exposure to air pollution during pregnancy may increase attention-deficit/hyperactivity disorder (ADHD) symptoms in children, but findings have been inconsistent. We aimed to study this association in a collaborative study of eight European population-based birth/child cohorts, including 29, 127 mother–child pairs. Methods: Air pollution concentrations (nitrogen dioxide [NO2 ] and particulate matter [PM]) were estimated at the birth address by land-use regression models based on monitoring campaigns performed between 2008 and 2011. We extrapolated concentrations back in time to exact pregnancy periods. Teachers or parents assessed ADHD symptoms at 3–10 years of age. We classified children as having ADHD symptoms within the borderline/clinical range and within the clinical range using validated cutoffs. We combined all adjusted area-specific effect estimates using random-effects meta-analysis and multiple imputations and applied inverse probability-weighting methods to correct for loss to follow-up. Results: We classified a total of 2, 801 children as having ADHD symptoms within the borderline/clinical range, and 1, 590 within the clinical range. Exposure to air pollution during pregnancy was not associated with a higher odds of ADHD symptoms within the borderline/clinical range (e.g., adjusted odds ratio [OR] for ADHD symptoms of 0.95, 95% confidence interval [CI] = 0.89, 1.01 per 10 µg/m 3 increase in NO2 and 0.98, 95% CI = 0.80, 1.19 per 5 µg/m 3 increase in PM2.5 ). We observed similar associations for ADHD within the clinical range. Conclusions: There was no evidence for an increase in risk of ADHD symptoms with increasing prenatal air pollution levels in children aged 3–10 years. See video abstract at, http://links.lww.com/EDE/B379 . Abstract : Supplemental Digital Content is available in the text.